Skrining Bioaktivitas Beberapa Bagian Jaringan Tumbuhan Paliasa(Melochia umbellata (Hout) Stapf var. Degrabrata K) - Erwin Erwin; Alfian Noor; Nunuk Hariani Soekamto; Tjodi Harlim (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
Paliasa is one of tropical plants that used as an etnobotanical traditional drug by the people of South Sulawesi. Paliasa leaves is believed and used as a drug for hypertension, diabetes mellitus, cholesterol, and hepatitis diseases. Preliminary study was done by Brine shrimp lethality test with Artemia salina to a tissue part of one of type paliasa, Melocia umbellata (Houtt.) Stapf. var. degrabrata K. The result show that the wood of this plant is the most active with LC50 value of 1,80 ppm. Keywords : Paliasa, traditional drug, M. umbellata, bioactivity.